The State of Immunity of the Population of the Russian Federation to Rubella during the Elimination of Infection - L. A. Barkinkhoeva; N. V. Turaeva; O. V. Tsvirkun; A. G. Gerasimova (Эпидемиология и вакцинопрофилактика)
Relevance. Serological monitoring of the state of the population's immunity to the rubella virus is one of the key elements of epidemiological surveillance of the infection, which makes it possible to assess the effectiveness of vaccine prevention, including the level of protection of the population from this infection. This article presents a comprehensive analysis of the results of this event in Russia for the period from 2015 to 2022 in individuals vaccinated against this infection, based on data from reports from regional centers and existing statistical models. The aim. To carry out a comprehensive analysis of data on serological monitoring of immunity among indicator groups of the population to rubella virus in the Russian Federation for the period from 2015 to 2022, taking into account the incidence and peculiarities of immunization tactics. Materials and Methods. Serological monitoring was carried out using standardized test systems and techniques, which ensured comparability of data throughout the entire study period (2015-2022). The contingent for the examination was selected with documentary confirmation of the fact of vaccination in the age groups 3–4 years, 9–10, 15–17, 25–29, 30–35 years. Only persons aged 40 years and older were examined without taking into account the vaccination history Results and Discussion. The conducted study confirmed a sufficient, stable level of immunity to the rubella virus in most age groups and regions of the country, which indicates the effectiveness of vaccination and the preservation (stabilization) of the infection elimination process. The slight increase in the average proportion of seronegatives among adults 30–35 and 40 years and older, revealed in the analysis, compared with other groups, requires further observation and clarification of the causes. Conclusions. The study confirmed the high level of immunity to rubella virus among the population of the Russian Federation, which indicates the effectiveness of the current program of vaccination against rubella infection and the infection elimination program. However, groups of the population have been identified, among which there is a slight decrease in the level of immunity, which requires additional attention from health authorities to maintain a stable rubella elimination status in the country. The results of the study will be used as additions to national and regional strategies aimed at maintaining the rubella elimination status.